Творчість В. Стуса і сучасність: до проблеми адаптації - Яструбецька, Галина Іванівна; Yastrubetska, Halyna I. (Національний університет "Острозька академія", 2013)
У статті зосереджено увагу на проблемі адекватності сприймання поезії В.Стуса, враховуючи її багатоступеневу, „синергетичну” природу.

The article focuses on the problem of the adequacy of the perception of Stus’s poetry, taking into account it multilevel, sinergistical nature, mystical and expressionistic elements, inherently led in and intensified by special literature and conditions of existence that creates a specific meaning of national and romantic lyrics.
Keywords: В. Стус; сприймання; ідентифікація; адекватність; інтерпретація; V.Stus; perception; identification; adequacy; interpretation; exhressionism